The Rhetoric of Donald Trump : Nationalist Populism and American Democracy - Rowland, Robert C., 1954- (Book collections on Project MUSE., 2021)
"Donald Trump's campaign for the presidency has been called "the single strangest development in American history" (Michael Gerson), and that is in large part because of Trump's use of rhetoric in appealing to the white working class. He won the presidency largely because of his rhetoric, and despite committing gaffe after gaffe, violating every norm identified by pundits and scholars alike about how a presidential candidate should talk, and presenting a message that was antithetical to the rhetorical vision of the greatest conservative hero of the last forty years, Ronald Reagan. Robert C. Rowland argues that Trump's rhetoric is defined by the themes of nationalist populism and by a rhetorical persona casting himself as first an outsider hero who could achieve near magical results and later, after assuming the presidency, as a more radical version of that persona, moving toward the role of heroic strongman. Rowland shows that, while these three elements are found in all of Trump's campaign and presidential rhetoric, there has been development over time toward a more extreme variant of all of these themes. The Rhetoric of Donald Trump traces the evolution and radicalization of Trump's message in rallies, in formal campaign settings, in policy and ceremonial speeches, and in his tens of thousands of tweets. This is an essential book for understanding what Trump reveals about the status of the modern presidency and the role of rhetoric in the American political system"--